Pengaruh Pendapatan Asli Daerah Terhadap Belanja Modal di Indonesia - Himawan, Hilmi Satria; Mubarok, Arif; Wahyuni, Eka; Sari, Ema Eka; Sukmawati, Erviana (Balance: Media Informasi Akuntansi dan Keuangan, 2024)
This study aims to examine the effect of original local government revenue on capital expenditure in 34 provinces in Indonesia. This type of reaserch is quantitative using secondary data on the SIKD djpk.kemenkeu.go.id as portal website. The size of sample is 34 provinces in Indonesia with an observation period in 2022. The analysis method in this study used simple linear regression analysis with SPSS 26 program. Research results show that original local government revenue has a positive effect on capital expenditure. This means that the higher the regional income which is obtained, the more capital expenditure will be increased.